Metrozones – Intra-metropolitan Developmental Areas in Context of Harbour Districts Redevelopment Strategies on Comparison of Hamburg (Harburg-Wilhlmburg) and Gdańsk (Letnica-Nowy Port) - Rembarz, Gabriela (Studia KPZK, 2018)
The article attempts a comparison of two harbor districts, in Gdansk and in Hamburg. In 2013, a multiannual program - IBA Hamburg (International Building Exhibition) - was completed. The IBA, initiated with the a concept of the Leap over the Elbe River, part of the Growing City development agenda, addressed the problem of restructuring the port-nearby zones in Harburg and Wilhelmsburg, which have been recognised as areas of high potential in metropolitan development. The concept of metrozones (intra-peripheries or intra border zones), similarly to the term in-between City (German: Zwischenstadt), describes the current problems associated with the strive for creation of an original, but efficient and compact European city. Restructuring of the harbor districts enables new development of the urbanized, but never planned as urban space, areas. Shaped in accordance with the technological capabilities and with the regulation standards and norms of the second half of the 20th century, nowadays the areas form the resultative landscape, burdened with the image of an unfriendly or even dangerous zones. In the era of high technology, metrozones are becoming valuable intra-city developmental areas, opened to alternative urban programs, avoiding the homogenising global trends. In connection with the above, the article describes the situation of the area organized around Nowy Port in Gdansk.
Keywords: Metrozone; revitalization of port districts; strategic urban planning